Pengaruh Audit Syariah dan Kepercayaan Nasabah Terhadap Kepuasan Nasabah Bank Syariah Indonesia - Herma Artika Putri; Fitrotul Mukaromah; Fikri Rizki Utama (Indo Publishing, 2026)
This study aims to determine the effect of Islamic audit and customer trust on customer satisfaction at Bank Syariah Indonesia. This study employs a quantitative approach with an associative method. The research sample consists of 100 respondents who are customers of Bank Syariah Indonesia in the Lampung region. Data were collected through questionnaires using a Likert scale and analyzed using SPSS software through validity, reliability, multiple linear regression, t-test, F-test, and coefficient of determination tests. The results indicate that Islamic audit and customer trust have a positive and significant effect on customer satisfaction. The Islamic audit variable has a t-value of 3.842 and customer trust has a t-value of 5.127, both with a significance value of 0.000 < 0.05. Simultaneously, both variables have a significant effect on customer satisfaction with an F-value of 42.615 > 3.09 and an R-Square value of 0.468. This demonstrates that Islamic audit and customer trust explain 46.8% of customer satisfaction, while the remaining percentage is influenced by other variables outside this study.